The Reality of Women’s Empowerment in Leadership Positions within Sports Institutions - Haza’a, Ahmed; Kamar , Nagham; Jasim , Ali (Journal of Physical Education, 2025)
The purpose of the study is to uncover the reality of women empowerment in leadership positions in Iraqi sport institutions by identifying the most significant inhibitors and contributors driving participation. They employed descriptive survey and sampled 211 female employees at the Ministry of Youth and Sports, Olympic Committee, as well as sports federations. It was discovered that cultural and social constrains are still the greatest obstacle (80%) for women’s empowerment, weak support from institution along with no genderfriendly organizational environments restrained their progress. Additionally, a dearth of Iraqi sports institutions necessitates an all-inclusive process that increases social awareness, develops better institutional policies and amplifies the role of media in supporting women to assume leadership roles.